SHELTER AS A WAY OF ORGANIZING A SAFE SPACE FOR PERSONS WHO HAVE SUFFERED FROM DOMESTIC AND GENDER VIOLENCE - Демченко, Ірина; Ревнюк, Наталія; Іващенко, Катерина (SWorldJournal, 2023)
The article examines the features and basic principles of shelters for victims of domestic violence and gender-based violence. The importance of their creation for the implementation of local and regional initiatives to end gender-based violence is noted